1998
DOI: 10.1161/01.cir.98.23.2527
|View full text |Cite
|
Sign up to set email alerts
|

Thrombolytic Therapy in Acute Myocardial Infarction

Abstract: Background-Thrombolytic therapy in patients with acute myocardial infarction (AMI) is hampered by procoagulant effects. In vitro studies have indicated that plasmin stimulation activates the kallikrein-contact-phase system, resulting in thrombin activation. This prospective comparative study was designed to examine the procoagulant effects of streptokinase or alteplase in AMI. Methods and Results-Sixty-one patients with AMI received 1.5 million U of streptokinase or front-loaded alteplase (up to 100 mg) and sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…Chopp and colleagues postulated that inhibition of fibrinolysis may accentuate microvascular thrombosis in stroke and studies have shown that microvascular thrombosis induced by endotoxemia is enhanced when fibrinolysis is inhibited. 24, 44-46 Consistent with that hypothesis, our data shows that differences in a2AP levels, which affect dissolution of the MCA thrombus, also modulate the development of microvascular thrombosis. Still, it is important to note that, despite their common effects on promoting thrombus dissolution through plasmin, TPA accentuated, while a2AP-I diminished, microvascular thrombosis.…”
Section: Discussionsupporting
confidence: 88%
“…Chopp and colleagues postulated that inhibition of fibrinolysis may accentuate microvascular thrombosis in stroke and studies have shown that microvascular thrombosis induced by endotoxemia is enhanced when fibrinolysis is inhibited. 24, 44-46 Consistent with that hypothesis, our data shows that differences in a2AP levels, which affect dissolution of the MCA thrombus, also modulate the development of microvascular thrombosis. Still, it is important to note that, despite their common effects on promoting thrombus dissolution through plasmin, TPA accentuated, while a2AP-I diminished, microvascular thrombosis.…”
Section: Discussionsupporting
confidence: 88%
“…In contrast, the rapid rise in sTM following initiation of streptokinase is temporarily associated with a fall in vitamin E. These changes support the hypothesis that increased oxidative stress during reperfusion is associated with endothelial damage, and this may have important prognostic implications [4]. The fall in fibrinogen is so immediate and profound that it is likely to be directly or indirectly due to the streptokinase, which is also associated with increased levels of the fibrin degradation product, d ‐dimer [5]. The observed platelet activation (increased sPsel) following both AMI and thrombolysis occurred despite routine administration of aspirin (acetylsalicylic acid) 300 mg.…”
Section: Discussionmentioning
confidence: 65%
“…36 Systemic activation of the KKS by tPA could have both peripheral and cerebral effects. Peripheral activation of PKal by tPA could contribute to orolingual angioedema that has been reported to occur at an incidence of up to 5% of cases during thrombolytic For personal use only.…”
Section: Discussionmentioning
confidence: 99%